2006
DOI: 10.1046/j.1360-0443.1995.90341510.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a brief motivational intervention with opiate users attending a methadone programme

Abstract: During the 1980s Motivational Interviewing emerged as one of the memes of the addictions field. This occurred despite the lack of scientific evidence supporting its utility. In this paper findings of a controlled trial of a brief motivational intervention with illicit drug users (n = 122) attending a methadone clinic are reported. Clients who met the study's inclusion criteria were randomly allocated to either a motivational (experimental, n = 57) or educational (control, n = 65) procedure. Over the 6-month fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Research on brief interventions, addressing alcohol and tobacco use, points to the efficacy of this method for these substances [3033]. There is, however, growing evidence of the effectiveness of brief interventions for other substances such as opiates [34], amphetamines [35], benzodiazepines [36], and cannabis [37]. Most of this work has focused on the general population; however, brief interventions with pregnant women have also been shown to be effective [3841].…”
Section: Discussionmentioning
confidence: 99%
“…Research on brief interventions, addressing alcohol and tobacco use, points to the efficacy of this method for these substances [3033]. There is, however, growing evidence of the effectiveness of brief interventions for other substances such as opiates [34], amphetamines [35], benzodiazepines [36], and cannabis [37]. Most of this work has focused on the general population; however, brief interventions with pregnant women have also been shown to be effective [3841].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1,699 studies were identified after removing duplicates ( Fig 1 ). After screening 44 full-text articles, eleven trials met the inclusion criteria and were included in this review [ 26 36 ]. Reasons for study exclusion included: other study design (n = 10), interventions failed to meet the definition of health coaching (n = 9), the patient population was under 18 years of age (n = 3), or no relevant outcome was measured (n = 11).…”
Section: Resultsmentioning
confidence: 99%
“…The eleven trials included in this review were conducted in five countries. Seven studies were conducted in the United States [ 27 30 , 32 , 33 , 36 ] while single trials were conducted in Norway [ 34 ], Scotland [ 31 ], Australia [ 26 ], and China [ 35 ] ( S5 Appendix ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brief motivational interventions have been successfully deployed in clinical and community outreach (e.g., NSEP) settings to increase patients’ readiness for treatment (Booth, Kwiatkowski, Iguchi, Pinto, & John, 1998; Kidorf, et al, 2005; Strathdee, et al, 2006). Brief cognitive interventions, while originally tested on individuals with alcohol use disorders (Maisto, et al, 2001; Rollnick, Heather, Gold, & Hall, 1992; Wilk, Jensen, & Havighurst, 1997), have been efficacious in increasing treatment entry for cocaine, heroin and amphetamine users (Baker, Boggs, & Lewin, 2001; Bernstein, et al, 2005; Saunders, Wilkinson, & Phillips, 1995). These sessions consist of a single, structured encounter targeting cessation of drug use conducted by a healthcare professional in a primary care setting.…”
Section: Discussionmentioning
confidence: 99%